Media Exposure: Unleashing the Influence of CSR Disclosure on Company Value: Paparan Media: Mengungkap Pengaruh Pengungkapan CSR terhadap Nilai Perusahaan - Vidya Dwi Asma Murni; Hadiah Fitriyah (Academia Open, 2022)
This quantitative study aims to examine the impact of CSR Disclosure and Profitability on Firm Value, while investigating the moderating role of Media Exposure. The research population consisted of 53 consumer goods companies, with a sample of 17 companies and a total of 68 observations. Data was collected through documentation techniques and analyzed using SmartPLS 3 (Partial Least Square) program. The findings reveal that both CSR Disclosure and Profitability significantly influence Company Value. Furthermore, Media Exposure weakens the relationship between CSR Disclosure and Company Value. However, no moderating effect of Media Exposure on the relationship between Profitability and Company Value was observed. These results contribute to the understanding of non-financial factors, such as CSR Disclosure and Media Exposure, in shaping company value. The implications of this research emphasize the importance of strategic CSR practices and the management of media exposure in enhancing company value in today's highly competitive business landscape. Highlights: CSR Disclosure drives Company Value: The study demonstrates the significant impact of CSR Disclosure on the overall value of a company, highlighting the importance of responsible business practices. Media Exposure as a moderating factor: Media Exposure is identified as a critical moderator that weakens the relationship between CSR Disclosure and Company Value, emphasizing the need for effective management of media perceptions. Profitability's limited influence: While Profitability is found to have a direct impact on Company Value, the research reveals that Media Exposure does not moderate this relationship, suggesting that other factors may play a more prominent role in determining company value. Keywords: CSR Disclosure, Profitability, Company Value, Media Exposure, Quantitative Study